Gut microbiota dysbiosis signature is associated with the colorectal carcinogenesis sequence and improves the diagnosis of colorectal lesions. Issue 12 (22nd June 2020) - Gao, Renyuan; Wang, Zhiguo; Li, Hao; Cao, Zhan; Gao, Zhiguang; Chen, Hongqi; Zhang, Xiaohui; Pan, Dengdeng; Yang, Rong; Zhong, Hui; Shen, Rongrong; Yin, Lu; et al.
Abstract: Background and Aim: The gut microbiota is associated with colorectal lesions in cases of precancer and colorectal cancer (CRC). However, there are apparent differences in studies on the gut microbiota in the pathogenic sequence from precancer to cancer. Here, we characterize the gut microbiota signatures of colorectal precancer and cancer and test their utility in detecting colorectal lesions in two independent Chinese cohorts. Methods: Stool samples collected from patients with precancer and CRC were subjected to 16S ribosomal RNA gene sequencing and metagenomic shotgun sequencing analyses, which revealed the microbial signatures of the two disease stages. Results: In comparison with healthy controls, lower microbial richness and diversity were observed in precancer and intensive interbacterial associations were found in CRC. We identified 41 bacteria that showed gradual increases while 12 bacteria showed gradual decreases at the genus level gradually during the development of CRC. Novel CRC‐associated pathogenetic species were identified. Species units that contributed to altered microbial functions were identified in CRC patients and healthy controls. The microbial panel showed a comparable ability to fecal immunochemical test (FIT) in detecting CRC. However, the combination of microbes and FIT significantly improved the detection ability and sensitivity of colon lesions based on 18 genera. Microbial network analysis revealed a significant positive correlation among beneficial microbes and a negative correlation in detrimental phenotypes. Conclusions: Microbial dysbiosis was revealed in colorectal lesions. The combination of microbial markers and FIT improved the CRC detection ability, which might assist in the early diagnosis of CRC.